External kinetics measurements in individual and relay swimming starts: a review - Mourao, L.; de Jesus, K.; de Jesus, K.; Fernandes, R.; Vaz, M.; Vilas-Boas, J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
This study aimed to present a literature review on the external kinetics of swimming starts for the purposes of summarising and highlighting existing knowledge, identifying gaps and limitations and challenging new researchers for future projects. A preliminary literature search was performed using relevant electronic data bases, only for English written documents published before September 2013. Keywords including 'swimming' and 'start' were used to locate documents. Proceedings of the scientific conferences of Biomechanics and Medicine in Swimming (BMS) and the International Society of Biomechanics in Sports (ISBS) from 1970 and 1983, respectively, to 2013 were examined. Included studies were experimental biomechanical approaches in laboratory setting relating to external kinetics assessments on swimming starts. Twenty-eight studies were included in this review, of which 10 are peer-review journal articles and 18 are proceedings from the BMS and ISBS Congress series. From the overall included studies, 82.14% analysed the individual ventral starts, followed by 14.28% at backstroke and only 3.57% at relay starts. Twenty-five per cent from the overall ventral starting studies measured the external horizontal and vertical forces acting on the swimmer's hands and only one research group has yet published about the upper limbs horizontal force on the backstroke start. Previous studies have presented unique contribution in swimming start kinetics; however, future researches should focus on devices capabilities improvements based on the current starting block configuration, mainly for dorsal and relay starting kinetics analysis purposes, and considering three dimensional, 6 degrees of freedom analysis of the forces exerted by each of the four limbs.